AKIBAT HUKUM PEMBATALAN AKTA JUAL BELI (AJB) ATAS TANAH OLEH PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PUTUSAN MAHKAMAH AGUNG NOMOR 888/K/PDT/2016 - Livia Clarista; Endang Pandamdari (Fakultas Hukum Universitas Tarumanagara, 2018)
Buying and selling is a process of transferring rights of land carried out by making a sale and purchase deed by a land deed official. Therefore, the procedure must be in accordance with the applicable laws and regulations to produce a valid deed and can be used to transfer the land rights. In this case, there was a mismatch in the procedure for making land sale and purchase deeds carried out by land deed official. This caused a legal defect in the deed which was then supported by a statement from the District Court Verdict Number 381/Pdt.G/2014/PN/Bdg. and the Bandung High Court with Decision Verdict 451/PDT/2015/ PT BDG., where both of them grant the plaintiff's claim, namely land deed official itself. However, the Supreme Court Judges considered that land deed official did not have a legal standing in filing a claim because it was deemed not to have legal interests in the sale and purchase deed. The Supreme Court Judges in Verdict Number 888 / PDT / 2016 canceled the previous court decision. This resulted in the deed returning to its original state. However, the deed can then only be canceled by the parties in it, but the cancellation also can only be done if both parties agree. While the legal consequences of the land deed official issuing the sale and purchase deed are the acceptance of sanctions in the form of temporary and permanent dismissals.